Threshold MnAs thickness for the formation of ordered α/β stripes in MnAs/GaAs(001). (30th April 2020) - Sacchi, Maurizio; Casaretto, Nicolas; Coelho, Leticia; Eddrief, Mahmoud; Ma, Jialin; Spezzani, Carlo; Vidal, Franck; Wang, Hailong; Zhao, Jianhua; Zheng, Yunlin
Abstract: Manganese arsenide layers epitaxially grown on GaAs(001) are known to feature a temperature dependent self-assembled microstructure of ordered stripes, alternating the ferromagnetic α and paramagnetic β phases. The surface dipolar fields generated by the α/β stripes have been used for achieving temperature controlled magnetization switching of a ferromagnetic overlayer. For this kind of application, it is advantageous to minimize the MnAs layer thickness. In this work we investigate, using x-ray scattering techniques, the presence of the ordered microstructure as a function of the MnAs layer thickness and we identify a minimum value of ∼40 nm for the formation of ordered α/β stripes in MnAs/GaAs(001). These results have an impact for envisaging magnetization-switching applications that rely on the control of the temperature—or laser-driven surface dipolar fields in MnAs-based devices.